Inductive and Capacitive Hysteresis of Halide Perovskite Solar Cells and Memristors Under Illumination - Munoz-Diaz, Laura; Rosa, Alvaro J.; Bou, Agustín; Sánchez, Rafael S.; Romero, Beatriz; John, Rohit Abraham; Kovalenko, Maksym V.; Guerrero, Antonio; Bisquert, Juan (Frontiers in Energy Research, 2022)
The current–voltage curves of memristors exhibit significant hysteresis effects of use for information storage and computing. Here, we provide a comparison of different devices based on MAPbI3 perovskite with different contact configurations, from a 15% efficient solar cell to a pure memristor that lacks directional photocurrent. Current–voltage curves and impedance spectroscopy give insights into the different types of hysteresis, photocapacitance, and inductance present in halide perovskites. It is shown that both halide perovskite memristors and solar cells show a large inverted hysteresis effect at the forward bias that is related to the presence of a chemical inductor component in the equivalent circuit. Based on the results, we classify the observed response according to recombination current in devices with selective contacts, to voltage-activated single-carrier device conduction in devices with symmetric contacts. These findings serve to gain an understanding of the mechanism of memristor currents in mixed ionic-electronic conductors such as halide perovskites. We establish the link in the electrical response between solar cells and memristors.